2022
DOI: 10.3390/cancers14143499
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Artificial Intelligence-Assisted Discrimination of Oral Cancerous Lesions from Normal Mucosa Based on the Oral Mucosal Image: A Systematic Review and Meta-Analysis

Abstract: The accuracy of artificial intelligence (AI)-assisted discrimination of oral cancerous lesions from normal mucosa based on mucosal images was evaluated. Two authors independently reviewed the database until June 2022. Oral mucosal disorder, as recorded by photographic images, autofluorescence, and optical coherence tomography (OCT), was compared with the reference results by histology findings. True-positive, true-negative, false-positive, and false-negative data were extracted. Seven studies were included for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Integration of AI-supported apps into mobile phones can effectively facilitate oral cancer screening in rural areas with limited access to healthcare services [24]. A previous study evaluated algorithms for the diagnosis and classi cation of oral cancers using intraoral photographs, and found that algorithms outperformed general practitioners and exhibited a performance similar to that of specialist physicians [25]. In our study, periodontists were the most successful group of dental professionals in diagnosing oral lesions.…”
Section: Resultssupporting
confidence: 49%
“…Integration of AI-supported apps into mobile phones can effectively facilitate oral cancer screening in rural areas with limited access to healthcare services [24]. A previous study evaluated algorithms for the diagnosis and classi cation of oral cancers using intraoral photographs, and found that algorithms outperformed general practitioners and exhibited a performance similar to that of specialist physicians [25]. In our study, periodontists were the most successful group of dental professionals in diagnosing oral lesions.…”
Section: Resultssupporting
confidence: 49%
“…Radiographic, microscopic, and ultrasonographic pictures have mostly been used in AI research for tumor and cancer identification. In addition, aberrant spots on radiographs, such as salivary and parotid glands and nerves in the oral cavity, can be found by AI [7][8] . Notably, AI also contributes to the management of cleft lip and palate in terms of risk assessment, diagnosis, pre-surgical orthopedics, speech evaluation, and surgery 9 .…”
Section: Discussionmentioning
confidence: 99%
“… 29 Precancerous lesions are an intermediate stage in the transformation of normal cells to cancer cells, which have similar and different genetic characteristics from tumors. 30 , 31 Moreover, they differ in their biological behavior and clinical manifestations, such as cell proliferation ability, motility, etc., which may be associated with progressive abnormal expression of oncogenes and tumor suppressor genes. In the present study, we identified progressive upregulated oncogenes and downregulated oncogenes in the disease process, which may be key factors influencing the process of NE-BE-EAC.…”
Section: Discussionmentioning
confidence: 99%